2011
DOI: 10.1590/s1516-18462011005000137
|View full text |Cite
|
Sign up to set email alerts
|

Perfil mastigatório de obesos mórbidos submetidos à gastroplastia

Abstract: OBJETIVO: traçar o perfil mastigatório do obeso mórbido. MÉTODO: estudo pareado por idade e sexo avaliou motricidade orofacial e mastigação de 40 obesos mórbidos submetidos à gastroplastia e 40 eutróficos sem queixas de mastigação e/ou deglutição. RESULTADOS: obesos mórbidos apresentaram: alteração de práxis e variáveis de lábios, língua, além de alteração no tamanho de mandíbula; na avaliação de mastigação habitual - ritmo rápido, movimentação vertical de mandíbula, tamanho grande do bolo, escassez de mastiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 8 publications
(9 reference statements)
1
13
1
6
Order By: Relevance
“…The results showed that there was a statistically significant difference in average between the groups concerning reduction of the cheeks, a finding that differs from a study with obese adults, which found that the integrity and shape of the tongue, cheeks and jaw was preserved 13 . In this research, it was found that 68% of the obese children showed reduced tonicity and mobility of cheeks against only 16% of the eutrophic children.…”
Section: Discussioncontrasting
confidence: 89%
“…The results showed that there was a statistically significant difference in average between the groups concerning reduction of the cheeks, a finding that differs from a study with obese adults, which found that the integrity and shape of the tongue, cheeks and jaw was preserved 13 . In this research, it was found that 68% of the obese children showed reduced tonicity and mobility of cheeks against only 16% of the eutrophic children.…”
Section: Discussioncontrasting
confidence: 89%
“…Os alimentos que apresentam uma grande superfície de contato gastam um maior tempo de digestão quando comparados àqueles que foram mais triturados, evitando, assim, sua longa permanência no estômago e no intestino delgado. Quando o alimento é mastigado, inadequadamente e de forma insuficiente, pode haver a presença de grandes volumes de ar no estômago, necessitando de um maior trabalho desse órgão para realizar a mistura do bolo alimentar com os sucos gástricos e as enzimas que irão digerir as proteínas 4 . Assim, a população dever ser orientada quanto à mastigação, visto que o ritmo mastigatório pode influenciar negativamente na saciedade, e consequentemente contribuir para o excesso de peso 11 .…”
Section: Resultsunclassified
“…As crianças devem estar atentas à forma e ao número de repetições que ocorrem na mastigação, pois quando ela é realizada de forma rápida e inadequada, pode ser um fator de risco para o excesso de peso, visto que a sinalização da saciedade cerebral não é realizada de forma instantânea, e o indivíduo poderá se alimentar excessivamente 4 .…”
Section: Introductionunclassified
“…Literature has few references about obese chewing. However, it is observed that among these, the chewing pattern of the morbidly obese is described mostly as very fast, prioritizing vertical movements, size of the bolus shown great and sometimes the lack of mastication 24 . Such characteristics potentially impair chewing food adaptation in patients undergoing bariatric surgery, providing the gagging, bloating, and vomiting entalos.…”
Section: Resultsmentioning
confidence: 99%
“…The feeling of fullness occurs according to indexes digestive, metabolic and endocrine modulators of the nervous function of the hypothalamus, which will limit the intake of more food 25 . Thus, it is necessary to guide the surgical candidate to his new pattern of chewing, explaining that it is not enough to only "chew slowly", it is necessary the complete degradation of the food in the mouth in order to promote the entire digestive process, helping, even, increasing the speed of passage of food by the digestive compartments without damaging los 24 .…”
Section: Resultsmentioning
confidence: 99%